AN ANALYSIS ON THE DECISION MODEL OF SMART PLUS INSURANCE PRODUCT PURCHASE - Fitry Primadona; Ujang Sumarwan; Mukhamad Najib (School of Business, IPB University (SB-IPB), 2016)
The purposes of this study were 1) to analyze the decision model of Smart Plus insurance product purchase and 2) to determine the criteria, sub-criteria, and alternative priorities in Smart Plus purchase decision model. The methods utilized in the study included a survey and interview (in-depth interview) by using an AHP analysis (Analytical Hierarchy Process) and processing software of